PROGRAM "SI PEMADAM TOLAK API" (PELATIHAN DAN PENDAMPINGAN TATA KELOLA, AKUNTABILITAS DAN EVALUASI) PENYUSUNAN RKP DESA GENTONG KABUPATEN NGAWI - Haryanto, Sendy Dwi; Ditasari, Rollis Ayu; Nuraina, Elva; Amalina, Nur Ayu; Novitasari, Dina Aprilia (Jurnal Abdi Insani, 2023)
Gentong Village is a village located in Paron District, Ngawi Regency. In preparing a transparent, accountable, participatory, orderly and targeted Village Government Work Plan (RKP Desa), a mature thought process is needed. The innovation needed is the lack of good governance and the lack of readiness of Human Resources to understand development planning, computers, and information technology. The program ‘’Si Pemadam Tolak Api’’ is a training and assistance related to the preparation of local governance-based RKP Desa to contribute to SDGs. This program provides literacy by conducting focus group discussions on obstacles in the preparation of RKP and providing understanding related to Local Governance. The main purpose of this community service activity is to encourage awareness, initiative, and participation from the people of Gentong Village in order to achieve becoming an independent village that can act as a subject of sustainable development. The result of this program is understanding and building the commitment of village governments in realizing the effectiveness of village governance, improving the quality of village governance and increasing village competitiveness to contribute to sustainable development. This program is implemented continuously to ensure the implementation of the program runs well to achieve good local governance. The program ‘’Si Pemadam Tolak Api’’ is a solution provided for the development of human resources from the village apparatus and needs to be carried out annually so that village officials in compiling RKP and RPJM are in accordance with applicable regulations in Indonesia and it is hoped that the development process in Gentong Village can run synergistically. This program is implemented continuously to ensure the implementation of the program runs well to achieve good local governance.